Perbedaan Pendapatan Usaha Tani Pembibitan Manggis Berlabel dan Tidak Berlabel di Desa Sukaraja Baru Kecamatan Indralaya Selatan Kabupaten Ogan Ilir: Yudi Armasyah, SP., M.Si. - Yudi Armansyah (Pusluhtan, 2023)
The aim of this study was to analyze the factors that influence differences in the productivity and income of labeled and unlabeled mangosteen nursery farms. The research was conducted in Sukaraja Baru Village, Indralaya Selatan District, Ogan Ilir Regency. The location selection was carried out purposively with the consideration that the location was a mangosteen nursery farming center in Indralaya Selatan District. The implementation of data collection for research purposes was completed in May - June 2021. Sampling used the Proportionate Stratified Random Sampling method with a total sample taken of 35 sample farmers from labeled mangosteen nurseries from 125 populations and 42 sample farmers from unlabeled mangosteen nurseries from 150 populations who conducts mangosteen nursery farming. The results showed that simultaneously the factors of production had a significant effect on the production of mangosteen nurseries. Partially the production factors of seeds, NPK fertilizer, labour, pesticides, and use of labels have a significant effect on mangosteen nursery production, while for the production factors of ZA fertilizer, manure, herbicides, length of farming, and farmer's education have no effect on mangosteen nursery production. There is a difference in the average productivity of labeled and unlabeled mangosteen nurseries with a t value of 13.768 with a significance of 0.000. There is a difference in income with a calculated t value of 3.642, a significant 0.05, where the average income of labeled mangosteen nursery farmers is greater than that of non-labeled ones.